Tacit Consent and Civil Disobedience - Schestag, Thomas (Stasis, 2018)
Refering back to the (juridical) cases of Socrates (in Athens) and Thoreau (in Concord), which both discuss dissent, Hannah Arendt’s essay “Civil Disobedience” elaborates on the question of a strict distinction or complicity between a single person’s moral decisions, and its participation, as member of a group, in political decision-making. How to approach the relation between morals and politics, ethics and jurisdiction; or, still otherwise, between Polis and Ethos, both words pointing (in different ways) towards places or sites? Both these topoi turn out to be linguistically determined through and through, constantly haunted by the question of how to speak (or not to speak), of how to listen (in order to obey or disobey, to consent or dissent) to what the laws do have to say (though not speaking at all). At the core of this tense and obscure paralinguistic relation to the (moral and juridical) law, between express and tacit consent (or dissent), silence and speech (or silence as speech), language and mutism, phasis and aphasia, lies the notion of homología, as discussed by Socrates in Plato’s dialogues Crito and Gorgias (to which Arendt’s essay constantly refers). This contribution takes on the Platonic notion of homología (as a promise of consent about a law’s content), and its relation to Hannah Arendt’s original and challenging version of the political and juridical notion of tacit consent, as discussed in “Civil Disobedience.”